2019
DOI: 10.3390/app9142906
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency Hopping Signals Tracking and Sorting Based on Dynamic Programming Modulated Wideband Converters

Abstract: Most of the earlier tracking and network sorting approaches with a high sampling rate for frequency hopping (FH) signals did not adapt to the wideband system during their implementation, whereas the sub-Nyquist based algorithms cannot satisfy the real-time requirement for dealing with the rapid change of sparsity. It is important to improve the compressed sensing (CS) methods for tracking and sorting wideband FH signals. In this paper, a dynamic programming modulated wideband converters (MWC) scheme is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In order to verify the effectiveness of the model and algorithm, the attacker's strategy in this section adopts the invariable interference strategy. MC-learning updates iterations with Equation ( 18) after the whole episode, while Sarsa and Q-learning update iterations with Equation (19) and Equation (20), respectively, when time changes in episode. The end of the iteration is based on whether the action-value function Q converges, and the total reward will be stable when Q converges.…”
Section: Algorithm 1 Mc-learning: On-policy Monte Carlo Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to verify the effectiveness of the model and algorithm, the attacker's strategy in this section adopts the invariable interference strategy. MC-learning updates iterations with Equation ( 18) after the whole episode, while Sarsa and Q-learning update iterations with Equation (19) and Equation (20), respectively, when time changes in episode. The end of the iteration is based on whether the action-value function Q converges, and the total reward will be stable when Q converges.…”
Section: Algorithm 1 Mc-learning: On-policy Monte Carlo Learningmentioning
confidence: 99%
“…On the other hand, the progress of radar anti‐jamming technology will also stimulate the innovation of radar jamming technology. For example, when the radar adopts anti‐jamming technologies such as frequency hopping [16], frequency agility [17], polarisation change [18] etc., the jammer needs to adopt jamming technologies such as frequency tracking [19], polarisation matching [20], waveform recognition [21] etc. to increase the jamming effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, constant-frequency RF signals are very susceptible to interference from the complex surrounding electromagnetic environment and to eavesdropping by third parties [1,2]. In this case, frequency-hopping signals have gradually replaced constant-frequency RF signals due to their strong anti-interference capability and good confidentiality and are widely used for military communications and remote control [3][4][5][6][7]. Since the introduction of FH technology in the military, research on jamming, counter jamming, counter sabotage and sabotage for FH technology has never stopped [8].…”
Section: Introductionmentioning
confidence: 99%
“…
We, the authors, wish to make the following corrections to our paper [1]. We found that the first author's name of the 'Reference [27]' [2] had been omitted in our paper.
…”
mentioning
confidence: 99%